Evolutionary thought in psychology : a brief history - Plotkin, H. C. (Henry C.) (Blackwell brief histories of psychology ;, 2004)
Evolutionary Thought in Psychology: A Brief History traces the history of evolutionary thought in psychology in an accessible and lively fashion and examines the complex and changing relations between psychology and evolutionary theory.:.; First book to trace the history of evolutionary thinking in psychology from its beginnings to the present day in an accessible and lively fashion.; Focuses on the rise of evolutionary theories begun by Lamarck and Darwin and the creation of the science of psychology.; Explains evolutionary thought's banishment by behaviorism and cultural anthropology in the.